ANALISIS PETA STRATEGI BERIKUT PENJABARANNYA: LESSON LEARNED PENERAPAN BALANCED SCORECARD SEKTOR PUBLIK - Biswan, Ali Tafriji; Aden, Salsabiyla (Jurnal Ilmiah Publika, 2023)
This study aims to describe the strategy map and its translation into strategic targets within the framework of the Balanced Scorecard (BSC) strategic management system implementation. The study used a qualitative approach based on document review, observation, interviews, and theoretical review. The study shows that the BSC strategic management system in the study object has been implemented through the translation of vision, mission, and strategy into operational objectives and performance measurement. The BSC system is considered successful in both organizational performance management and individual performance management. There is still a slight weakness in the application of BSC, namely in the preparation of key performance indicators (KPIs) for employee performance contracts, performance managers in the General Subdivision become coordinators and take over the work of all sections on the grounds of uniformity of format. Whereas the employee performance contract should be made by each employee in discussion with their direct supervisor. However, the coordination between the performance manager and the liaison officer of each section is enough to reflect the contribution of each section in the preparation of KPIs.